"Chipping away": non-consumer researcher perspectives on barriers to collaborating with consumers in mental health research. (2nd January 2019) - Happell, Brenda; Gordon, Sarah; Bocking, Julia; Ellis, Pete; Roper, Cath; Liggins, Jackie; Scholz, Brett; Platania-Phung, Chris
Abstract: Background : Collaboration between researchers who have lived experience of mental illness and services (consumer researchers) and mental health researchers without (other mental health researchers) is an emergent development in research. Inclusion of consumer perspectives is crucial to ensuring the ethics, relevancy and validity of mental health research; yet widespread and embedded consumer collaboration of this nature is known to be impeded by attitudinal and organisational factors. Limited research describes consumer researchers' experiences of barriers. Other mental health researchers are key players in the co-production process yet there is also a paucity of research reporting their views on barriers to collaborating with consumers. Aims : To explore other researchers' views and experiences on partnering with consumer mental health researchers in Australia and New Zealand. Methods : Exploratory qualitative design. Eleven semi-structured interviews were conducted with mental health researchers. Interviews were recorded, transcribed and thematically analysed. Results : Four themes concerning barriers to collaborating with consumers (hierarchies, status quo, not understanding, paternalism), and one theme on addressing the barriers (constantly chipping away) were identified. Conclusions : It is suggested that multifaceted strategies for advancing collaboration with consumers are most effective. It is imperative to attend to several barriers simultaneously to redress the inherent power disparity.